Oncolytic Herpes Simplex Virus Encoding IL12 Controls Triple-Negative Breast Cancer Growth and Metastasis - Ghouse, Shanawaz M.; Nguyen, Hong-My; Bommareddy, Praveen K.; Guz-Montgomery, Kirsten; Saha, Dipongkor (Frontiers in Oncology, 2020)
Triple-negative breast cancer (TNBC) is a difficult-to-treat disease with high rates of local recurrence, distant metastasis and poor overall survival with existing therapies. Thus, there is an unmet medical need to develop new treatment regimen(s) for TNBC patients. An oncolytic herpes simplex virus encoding a master anti-tumor cytokine, interleukin 12, (designated G47∆-mIL12) selectively kills cancer cells while inducing anti-tumor immunity. G47∆-mIL12 efficiently infected and killed murine (4T1 and EMT6) and human (HCC1806 and MDA-MB-468) mammary tumor cells in vitro. In vivo in the 4T1 syngeneic TNBC model, it significantly reduced primary tumor burden and metastasis, both at early and late stages of tumor development. The virus-induced local and abscopal effects were confirmed by significantly increased infiltration of CD45+ leukocytes and CD8+ T cells, and reduction of granulocytic and monocytic MDSCs in tumors, both treated and untreated contralateral, and in the spleen. Significant trafficking of dendritic cells (DCs) were only observed in spleens of virus-treatment group, indicating that DCs are primed and activated in the tumor-microenvironment following virotherapy, and trafficked to lymphoid organs for activation of immune cells, such as CD8+ T cells. DC priming/activation could be associated with virally enhanced expression of several antigen processing/presentation genes in the tumor microenvironment, as confirmed by NanoString gene expression analysis. Besides DC activation/priming, G47∆-mIL12 treatment led to up-regulation of CD8+ T cell activation markers in the tumor microenvironment and inhibition of tumor angiogenesis. The anti-tumor effects of G47∆-mIL12 treatment were CD8-dependent. These studies illustrate the ability of G47∆-mIL12 to immunotherapeutically treat TNBC.